Caracterización de las meningitis agudas por Streptococcus pneumoniae en la población pediátrica desde 2008 hasta 2019 en 10 hospitales de la ciudad de Bogotá, Colombia (2019)
Introduction: Acute bacterial meningitis due to Streptococcus pneumoniae is an important pathology from the point of view of public health due to its high morbidity and mortality. Since 2006 the pneumococcal vaccine has been introduced in the country progressively, and in 2012 it is introduced in the mandatory vaccination scheme. Its impact on the epidemiology of the disease has been studied in recent years. Aim: Perform a clinical, epidemiological and microbiological characterization of patients with acute bacterial meningitis due to Streptococcus pneumoniae. Methodology: Pneumococcal meningitis data were collected from 10 hospitals in Bogotá D.C., from January 2008 to July 2019, participants of the Neumocolombia network, created for the surveillance of Invasive Pneumococcal Disease. Results: Data were collected from a total of 58 cases of the pathology. The most consistent symptoms in the cohort were fever and hyporexia, followed by epileptic seizures. The isolates in which the antibiogram was obtained show an increase in resistance to penicillin and third generation cephalosporins since 2015. The mortality rate of the disease is 20.68%, and the most important sequel, dysfunction cognitive, reaches a frequency of 73.77%, followed by sensorineural hearing loss, motor disorders and epilepsy. Conclusions: Acute pneumococcal meningitis is a pathology of great impact for public health. Guidelines to adjust the treatment to the current characteristics of the infection are required, and efforts to prevent it should be continued.